Peningkatan Keterampilan Mahasiswa Asrama Islamic College Siti Aisyah Malang Melalui Diversifikasi Produk Bakso Sehat - Anggraini, Apriliana Devi; Mulatmi, Septi Nur Wulan; Fitriani, Lina (Universitas Muhammadiyah Malang, 2024)
Purpose – The training and mentoring program for manufacturing meatballs for a group of female students at the Siti Aisyah Islamic College dormitory seeks to support and aid the dormitory's management's planned entrepreneur initiative. The program helped participants learn the fundamentals of livestock product processing, how to use technology, how to be creative, and how to develop their skills in processing animal products with varied product diversifications. Design/methodology/approach – The series of activities lasted four months. The service activities were divided into multiple stages, including socializing, training, and assistance with meatball production and diversification. The method was to conduct pre-coordination activities with the management of the Siti Aisyah Islamic College Dormitory, activity preparation, activity implementation in the form of socialization and discussion of livestock product processing, meatball training, mentoring female students, and activity evaluation. Female students were given questionnaires before and following the deployment of the aid. The data was analyzed using quantitative descriptive methods. Findings – This project created preservative-free meatball goods and several product variations, including original, vegetable, and cheese meatballs. The program resulted in a 70% improvement in understanding of processing livestock products, as well as an 80% rise in meatball-making abilities and variants. Originality/value –The meatball training program could be an alternative entrepreneurial curriculum designed by the association's board. Training may help students improve their abilities and gain experience, as well as motivate them to grow their businesses.